(i) We compute the derivatives and find that
"u_{xx}=-\\lambda^2e^{-\\lambda y}cos(\\lambda x),\\quad u_{yy}=\\lambda^2e^{-\\lambda y}cos(\\lambda x)"
From the latter it follows that the Laplace equation is satisfied. I.e., "u_{xx}+u_{yy}=0" .
(ii)
"u_{\\lambda}=-\\lambda e^{-\\lambda y}cos(\\lambda x)-e^{-\\lambda y}sin(\\lambda x),"
"u_{\\lambda\\lambda}=\\lambda^2e^{-\\lambda y}cos(\\lambda x)+\\lambda^2e^{-\\lambda y}sin(\\lambda x)+\\lambda e^{-\\lambda y}sin(\\lambda x)-\\lambda e^{-\\lambda y}cos(\\lambda x)="
"=\\lambda^2u-\\lambda u+\\lambda^2 v+\\lambda v,"
where "v=e^{-\\lambda y}sin(\\lambda x)" . We compute the second order derivatives and get "v_{xx}=-\\lambda^2e^{-\\lambda y}sin(\\lambda x), v_{yy}=\\lambda^2e^{-\\lambda y}sin(\\lambda x)" .
Thus, "u_{\\lambda\\lambda}" also satisfies the Laplace equation.
(iii) At first, we calculate the indefinite integral "\\int e^{-\\lambda y}cos(\\lambda x)d\\lambda=-\\frac{1}{y}e^{-\\lambda y}cos(\\lambda x)+"
"-\\frac{x}{y}\\int e^{-\\lambda y}sin(\\lambda x)d\\lambda=-\\frac{1}{y}e^{-\\lambda y}cos(\\lambda x)+\\frac{x}{y^2}e^{-\\lambda y}sin(\\lambda x)-\\frac{x^2}{y^2}\\int e^{-\\lambda y}cos(\\lambda x)d\\lambda"
We denote "I=\\int e^{-\\lambda y}cos(\\lambda x)d\\lambda" . Then "I=-\\frac{1}{y}e^{-\\lambda y}cos(\\lambda x)+\\frac{x}{y^2}e^{-\\lambda y}sin(\\lambda x)-\\frac{x^2}{y^2}I" .
From the latter we get: "I=-\\frac{y}{x^2+y2}e^{-\\lambda y}cos(\\lambda x)+\\frac{x}{x^2+y^2}e^{-\\lambda y}sin(\\lambda x)"
Using the latter, we get "v(x,y)=\\int_0^{+\\infty} e^{-\\lambda y}cos(\\lambda x)d\\lambda=\\frac{y}{x^2+y^2}"
The latter has the following derivatives:
"v_{xx}=\\frac{2y(3x^2-y^2)}{(y^2+x^2)^3};\\qquad v_{yy}=-\\frac{2y(3x^2-y^2)}{(y^2+x^2)^3}"
From the latter it is clear that "v_{xx}+v_{yy}=0" .
Comments
Leave a comment